On-grid vs. off-grid photovoltaic systems for smart greenhouses: a techno-economic case study - Simorangkir, Arthur; Halim, Levin (Institute of Advanced Engineering and Science, 2025)
Integrating photovoltaic (PV) systems into agricultural applications has gained significant attention as a sustainable energy solution. However, the feasibility of on-grid and off-grid PV systems for smart greenhouse applications in Indonesia remains unclear. This study compares both systems' technical performance, economic viability, and regulatory challenges through simulations and case studies in Lembang, Bandung. The analysis considers solar radiation levels, shading effects, installation costs, energy independence, and long-term operational efficiency. Results indicate that while on-grid systems offer lower initial investment and seamless integration with the utility grid, regulatory constraints and limited capacity approvals pose significant barriers. Despite higher initial costs, off-grid systems provide energy independence and long-term cost benefits by eliminating dependency on grid electricity and avoiding bureaucratic hurdles. The study concludes that off-grid PV systems are a more practical and sustainable solution for smart greenhouse applications in Indonesia, mainly where grid connection processes are complex or unreliable.